Young Africans' representations of the origins of same-sex attraction and implications for sexual and mental health. Issue 3 (4th March 2017) - Winskell, Kate; Sabben, Gaëlle; Pruitt, Kaitlyn L.; Allen, Kristi; Findlay, Trinity; Stephenson, Rob
Abstract: Sexual minorities are stigmatised in much of sub-Saharan Africa, restricting their access to sexual health services and undermining their mental health. Although public attitudes and social representations inform the experience of sexual stigma, little is known about how young Africans make sense of sexual diversity. We conducted a thematic analysis of 56 texts contributed by young people from 10 countries in response to a prompt in a scriptwriting competition inviting participants to 'tell a story about someone who is attracted to people of the same sex'. We analysed accounts of the origins of same-sex attraction, a prominent theme in the narratives. Two-thirds of the texts provide an explicit or implicit explanation, presenting same-sex attraction as innate (15/38) and/or the consequence of environmental influences (32/38), including parental behaviour, gender separation, trauma, foreign influences and evil spirits. Expressions of the potential to avert or cure same-sex attraction are common. Young people's sense-making around sexual diversity draws on available sociocultural and symbolic resources, some of which may be highly stigmatising, and reflects local, national and transnational influences. The need to explain same-sex attraction and the preponderance of harmful explanatory frameworks compounds sexual minority youth's vulnerability to sexual stigma, harmful coping strategies and mental health challenges.